Data protection challenges in the internet of things era: an assessment of protection offered by PDPA 2010 - Sidi Ahmed, Sidi Mohamed; Zulhuda, Sonny (2019)
The Internet of Things (IoT) is an emerging technology of the 21st century. It is described as the first real evolution of the Internet that could positively or negatively affect all aspects of life. The basic idea of the IoT revolves around connecting things and objects (persons, animals, cars, trees, etc.) to the Internet and enabling them to communicate and then process (generate, receive, send, etc.) data about themselves and the environment surrounding them. Without a doubt, the IoT will bring countless benefits and provide timely data and information about places and objects. However, the IoT, like other technologies, has disadvantages especially in terms of privacy and security of data. Particularly, the IoT might challenge personal data protection law and misgive its ability to effectively stand in the rapid successive technology waves. As the most important law relating to the protection of personal data in Malaysia, the Personal Data Protection Act (PDPA) 2010 could be used as a benchmark for assessing the adequacy of data protection law in the country. Thus, this paper attempts to shed light on data protection challenges in the IoT era and then assess the adequacy of this Act in dealing with those challenges. The paper employs a legal doctrinal method to analyze the legal frameworks relevant to personal data protection. It may also use a comparative method to compare the PDPA with its counterparts in other countries. A study such as this is arguably useful and timely as Malaysia is already embarked in the IoT caravan with the vision of being “the Premier Regional IoT Development Hub.”